PERSEPSI PERAWAT MENGENAI KEBUTUHAN SPIRITUAL DAN PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI INSTALASI GAWAT DARURAT - Ita Yuni Asih (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2021)
Patient overcrowding and rapid patient turnover in emergency department cause nurses to be less than optimal in providing patients spiritual needs. This condition can affect the emergency nurses' perceptions of spirituality and fulfill the patient's spiritual needs. A good fulfillment of the emergency patients spiritual needs can also improved a good treatment results. Nurses who have a good spiritual perception will have the ability to fulfill the patient's spiritual needs. Objective: describe nurses’ perception of spiritual needs and fulfill the spiritual needs of patients in the emergency department. Methods: This study was used descriptive survey research. Samples were taken using total sampling technique and obtained 75 participants. Data were taken using the Spiritual Care Giving Scale (SCGS) questionnaire and analyzed by univariate analysis. Results: more than a half of emergency nurses considered spiritual needs and fulfilled the patient’s spiritual needs as very important (57,3%). Every aspect of fulfilling spiritual needs is also perceived to be very important by emergency nurses. Conclusion: An aspect that need to be improved are values in fulfilling spiritual needs. The value of spirituality is interpreted as a very important part of holistic nursing. Consequently, emergency nurses need to improve their understanding of spirituality so that the implementation of fulfilling patients spiritual needs in emergency department can be positively reinforced.